Social Service Activities of Iqra' and Al Qur'an Waqf at TPA / Diniyah in Berau Regency, East Kalimantan: Economic Empowerment of the Community through Waqf - M Ainul Muwaffiq; Mohamad Mahrusillah (IRDH International Journal of Social Sciences & Humanities, 2025)
This research examines the implementation of the endowment of Iqra’ books and the Qur’an as part of a social service program in several TPA (Islamic learning centers) and Madrasah Diniyah (Islamic schools) in Berau Regency, East Kalimantan. The goal of this activity is to expand access for children to Islamic education, particularly for those with limitations in obtaining learning resources. Through a qualitative approach with direct class teaching methods, this study explores the stages of planning, implementation, and outcomes of the program. The findings show that the distribution of 30 Iqra’ books and 25 copies of the Qur’an to 20 students has positively impacted their motivation to learn, the smoothness of the Qur’an reading process, and the growth of social awareness among the community. In addition to providing material support, this activity also strengthens the role of Islamic educational institutions in shaping character and religious values from an early age.